The influence of fattening periods on performance, carcass composition, and meat quality of Charolaise crossbred steers - Kheawrod, W.; Sivapirunthep, P.; Thiwaratkoon, P.; Chongcharoen, M.; Chancharoen, P.; Yathongchai, W.; Chaosap, C. (International Journal of Agricultural Technology, 2020)
Results showed that the initial weight did not differ between groups (P>0.05). While, the 15 month group had more heavy weight than 12 month group (P<0.01). Furthermore, the 15 month group gained more weight than 12 month group (P<0.05). The average daily gain of 15 month group was higher than 12 month group (P<0.01) which were 723.62 and 603.30 gram/day, respectively. The weight of hot and cold carcass of 15 month group was higher than 12 month group (P<0.01) while the percentage of hot and cold carcass did not differ between group (P>0.05). For carcass composition, lean percentage (P<0.01) and bone percentage (P<0.05) were higher in 15 month group than in 12 month. Meat color, shrinkage loss, cooking loss, and shear force did not affect by fattening period (P>0.05). In addition the fattening period did not impact on collagen content and also collagen solubility (P>0.05).